2019
DOI: 10.1016/j.pathophys.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gut microbiome changes following regional intestinal lymphatic obstruction in primates

Abstract: The pathogenesis of inflammatory bowel disease (IBD) has been linked with lymphostasis, but whether and how lymphatic obstruction might disturb the intestinal microbiome in the setting of Crohn's Disease (CD) is currently unknown. We employed a new model of CD in African Green monkeys, termed 'ATLAS' (African green monkey truncation of lymphatics with obstruction and sclerosis), to evaluate how gut lymphatic obstruction alters the intestinal microbiome at 7, 21 and 61 days. Remarkable changes in several microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…99 In a primate model of Crohn disease, obstruction of lymphatic outflow dramatically altered intestinal microbial subgroups, including greater abundance of Prevotellaceae and Bacteroidetes-Prevotella-Porphyromonas. 100 These results illustrate a cycle whereby metabolic changes associated with disease, including kidney disease, disrupt the intestinal microbiome, which impairs the lymphatic vascular network, which, in…”
Section: Dysbiosis/toxinsmentioning
confidence: 94%
“…99 In a primate model of Crohn disease, obstruction of lymphatic outflow dramatically altered intestinal microbial subgroups, including greater abundance of Prevotellaceae and Bacteroidetes-Prevotella-Porphyromonas. 100 These results illustrate a cycle whereby metabolic changes associated with disease, including kidney disease, disrupt the intestinal microbiome, which impairs the lymphatic vascular network, which, in…”
Section: Dysbiosis/toxinsmentioning
confidence: 94%
“…This was the first human study to link changes in lymphatic structure/intestinal function and the gut microbiome. 170 Subsequent studies found that the incidence of H. pylori ‐negative mucosa‐associated lymphatic tissue (MALT) lymphoma was related to the presence of H. pylori in some patients. Interestingly, alpha diversity was significantly reduced in H. pylori ‐negative MALT lymphoma patients compared to controls ( p = 0.04).…”
Section: Human Carcinogenic or Cancer‐promoting Microbiomesmentioning
confidence: 99%
“…In a study on the relationship between changes in human lymphatic structure/intestinal function and gut microbes, researchers determined that the abundance of Prevotella and Bacteroidetes‐Prevotella‐porphyromona (BPP) increased in the gut microbiome. This was the first human study to link changes in lymphatic structure/intestinal function and the gut microbiome 170 . Subsequent studies found that the incidence of H. pylori ‐negative mucosa‐associated lymphatic tissue (MALT) lymphoma was related to the presence of H. pylori in some patients.…”
Section: Human Carcinogenic or Cancer‐promoting Microbiomesmentioning
confidence: 99%